Utilización de 2 niveles de inclusión de harina de larva de mosca soldado negro (Hermetia illucens) en sustitución de la soya como fuente proteica en dieta de pollos parrilleros en fase de crecimiento y engorde. - Del Hierro Escobar, Diego Esteban (2022)
The present study evaluates the use of two inclusion levels (30% and 40%) of black soldier fly (Hermetia illucens) larvae meal as a substitute for soybean as protein sources in balanced diets for broiler chickens in growth and fattening phase. The study was carried out in the city of Ambato for a period of 4 weeks applying a completely randomized design with 96 animals distributed in three treatments and four replicates. For the interpretation of results, an analysis of variance (ANOVA) and Duncan's test at 95% reliability were used. Bromatological, microbiological and granulometric analyses were carried out, finding protein levels between 52.89% and 53.94%, absence of pathogenic microorganisms and a particle size of 260.45µ. The research did not reveal significant differences for final weight, feed consumption or feed conversion, however, weight gain revealed a statistical difference in the first week of the study presenting lower values for T1 (123.25 g/bird) as opposed to the values reported for T3 (174.45 g/bird), which shows a higher weight gain in animals fed with 40% black soldier fly larvae meal as protein replacement for their fourth week of life. During the third week of the study, mortality was recorded for T1 with 2 deaths, T2 (30%) with 3 deaths and T3 (40%) with 1 death, giving a total of 6 deaths attributed to the ascitic syndrome presented in the birds. The results of the research show better effects for the treatments with the inclusion of black soldier fly larvae meal, with T3 being superior to the rest of the treatments, so that the substitution of 40% of black soldier fly meal for soybean as a protein source in broiler feed can be recommended.g/bird), which shows a higher weight gain in animals fed with 40% black soldier fly larvae meal as protein replacement for their fourth week of life. During the third week of the study, mortality was recorded for T1 with 2 deaths, T2 (30%) with 3 deaths and T3 (40%) with 1 death, giving a total of 6 deaths attributed to the ascitic syndrome presented in the birds. The results of the research show better effects for the treatments with the inclusion of black soldier fly larvae meal, with T3 being superior to the rest of the treatments, so that the substitution of 40% of black soldier fly meal for soybean as a protein source in broiler feed can be recommended.